The training needs of primary and secondary in-service school teachers engaging in virtual exchange - Ciara R. Wigham; Begoña Clavel-Arroitia (Journal of Virtual Exchange, 2025)
Advances in educational technology, including videoconferencing, have resulted in a rise in virtual exchange (VE). Researchers have touted the benefits of conducting VEs including developing learners’ intercultural awareness, intercultural competence, and digital skills (O’Dowd, 2018). Few studies have been conducted in secondary and primary school settings, however. To fill this gap, an online questionnaire was administered, and subsequent focus group interviews were conducted with primary and secondary teachers to understand their needs and the challenges which impact their ability to conduct VE projects. The findings of our needs analysis show that the majority of primary teachers reported a lack of technological training, including which tools and/or applications best support VEs, while secondary teachers reported lacking both technological and pedagogical training for VEs, such as how to integrate VE tasks into their curricula. To accommodate these needs and challenges, we advocate for a training space which provides experienced and novice teachers the opportunity to discuss VE in their teaching contexts and training materials to assist in designing, implementing, or adapting VE tasks.